Sodium bicarbonate production from waste sodium hydroxide solution - Cainglet, Jerome H. (College of Engineering, 1989)
This plant design report proposes the commercial manufacturing process for the production of technical grade sodium bicarbonate from an electrolytic waste solution. Material and energy balances of the entire plant and on each individual piece of equipment were accomplished and tabulated. All equipment and pipes were specified, and the cost of the whole plant was estimated. An economic survey was also conducted on the viability of the product. Based on these considerations, the economic and technical feasibility of the project was assessed. 13.152 tons per day of the solution, containing 10.54 percent sodium hydroxide, 17.61 percent sodium chloride, and 0.224 sodium carbonate can yield 2.63 tons of the product, consisting of 99.9 percent sodium bicarbonate and 0.1 percent sodium carbonate. A 10.32 percent return on investment and a payout time of 4.9 years were obtained for this project.